Green transition - a roadmap for sustainable development - Dao Xuan Thai (Journal of State Management, 2025)
This article provides a systematic analysis of the theoretical foundations, practical contexts, and policy orientations related to the green transition within Vietnam’s sustainable development process. Based on theoretical frameworks developed by international organizations, the study identifies the green transition as a comprehensive restructuring of the economy, society, and governance systems to achieve low-carbon growth, efficient resource use, and social equity. Drawing on an assessment of current conditions, the article highlights Vietnam’s initial achievements in green transition across the energy, agriculture, and urban development sectors, as well as key challenges in institutions, finance, science and technology, and public awareness. Accordingly, it proposes comprehensive and feasible policy solutions to accelerate the green transition in close alignment with the sustainable development goals and the national commitment to achieving net-zero emissions by 2050.